The ability of biology teachers to manage a classroom based on Lesson Study learning model. (February 2020) - Hasanuddin, H; Nurmaliah, C; Samingan, S; Iswadi, I; Artika, W
Abstract: Lesson study is a model of teacher professional development through the study of learning and capacity building of knowledge. This study aimed to determine the ability of a biology teacher at SMAN 1 Meureudu in implementing a lesson study in the classroom. The experiment was conducted from July to September 2015. The Data was obtained through the observation sheet of the learning process, including six indicators of introduction activity aspect, 28 indicators of core activities aspect, and four indicators of the final activity aspect. Learning management was carried out in three stages of lesson study. The results of the first stage of open and post activities were went less well with an average score of 2.33 and 2.25 respectively. An Improvement was being exposed at the introduction aspect during the second stage of the open lesson with an average score of 2.83 (good category). Then, the post-lesson aspect also improved at the third stage of open lesson with an average score of 3.0 (good category). It is concluded that the ability of the biology teacher at SMA Negeri 1 Meureudu to manage classroom had improved after the third stage of the open lesson implementation with good category (average score 2.88).